Do the ends justify the means? Impact of drought progression rate on stress response and recovery in Vitis vinifera. Issue 1 (10th November 2021) - Morabito, Cristina; Orozco, Jessica; Tonel, Giulia; Cavalletto, Silvia; Meloni, Giovanna Roberta; Schubert, Andrea; Gullino, Maria Lodovica; Zwieniecki, Maciej Andrzej; Secchi, Francesca
Abstract: Plants are frequently exposed to prolonged and intense drought events. To survive, species must implement strategies to overcome progressive drought while maintaining sufficient resources to sustain the recovery of functions. Our objective was to understand how stress rate development modulates energy reserves and affects the recovery process. Grenache Vitis vinifera cultivar was exposed to either fast‐developing drought (within few days; FDD), typical of pot experiments, or slow‐developing drought (few weeks, SDD), more typical for natural conditions. FDD was characterized by fast (2–3 days) stomatal closure in response to increased stress level, high abscisic acid (ABA) accumulation in xylem sap (>400 μg L −1 ) without the substantial changes associated with stem priming for recovery (no accumulation of sugar or drop in xylem sap pH). In contrast, SDD was characterized by gradual stomatal closure, low ABA accumulation (<100 μg L −1 ) and changes that primed the stem for recovery (xylem sap acidification from 6 to 5.5 pH and sugar accumulation from 1 to 3 g L −1 ). Despite FDD and SDD demonstrating similar trends over time in the recovery of stomatal conductance, they differed in their sensitivity to xylem ABA. Grenache showed near‐isohydric and near‐anisohydric behavior depending on the rate of drought progression, gauging the risk between hydraulic integrity and photosynthetic gain. The isohydry observed during FDD could potentially provide protection from large sudden swings in tension, while transitioning to anisohydry during SDD could prioritize the maintenance of photosynthetic activity over hydraulic security.